Modelling of a humidification-dehumidification greenhouse in Oman - Al-Ismaili, Abdulrahim M. (Cranfield University, 2009)
The humidification-dehumidification (HD) greenhouse is a relatively new technology. In addition to the humidification process and cultivation normally present in greenhouses in arid countries, the HD greenhouse also integrates a dehumidification process. In these greenhouses, saline or brackish water is evaporated in the ordinary evaporative cooling pads (i.e. 1st humidifier) before passing through the main crop growing section. The air is further loaded with more moisture by passing it through a 2nd humidifier. This humidification process is then followed by a dehumidification process to condense as much water vapour as possible. The main purpose of the HD greenhouses is to find a cheap means of desalinating saline water for the sake of using the condensate for irrigation. Most of previous attempts to improve the performance of the HD greenhouses have used a trial-and-error approach. An alternative approach is to use simulation models. Due to the absence of such models, this research study aims at developing a simulation model capable of simulating the significant processes of the HD greenhouses. The developed model is an integration of three sub-models each of which simulates one element of the HD greenhouse. The simulated elements are humidifiers, cultivation area (i.e. microclimate) and dehumidifiers. The integrated model can be used for design and optimisation purposes. Because it was difficult to find an HD greenhouse where the accuracy of the integrated model can be tested, the three sub-models were tested separately. When the simulation results were confronted against the experimental results, a good accuracy was obtained for the three sub-models. It was found that the HD greenhouse model was able to predict the humidification rate with a good accuracy within the range of conditions used for calibration. The model was, then, used to simulate a hypothetical Quonset-type cucumber-cultivated greenhouse using weather data obtained from the site of the HD greenhouse in Oman. The simulation results were similar to the expected results.The applications and limitations of the HD greenhouse model are discussed in this study. Future investigations to further study and, if necessary, improve the accuracy of the HD greenhouse are highly recommended.